Respuesta :
Hey there!
In order to simplify this equation, we can use our properties of negatives. We know that:
(x)+(-y) = x - y
Therefore, we can simplify this equation to:
a - 7 = 17
Using the additive algebraic property of equality, we can add 7 to both sides to get:
a = 24
Therefore, your answer is the last one, a = 24.
Hope this helps!
In order to simplify this equation, we can use our properties of negatives. We know that:
(x)+(-y) = x - y
Therefore, we can simplify this equation to:
a - 7 = 17
Using the additive algebraic property of equality, we can add 7 to both sides to get:
a = 24
Therefore, your answer is the last one, a = 24.
Hope this helps!